EFFICACY ANDTOLERABILITY OF NIMESIL-SOLUBLE FORM OF NIMESULID IN RHEUMATOID ARTHRITIS(PRELIMINARY RESULTS) - R. M. Balabanova (Научно-практическая ревматология, 2002)
Efficacy and tolerability of soluble nimesulid (nimesil) 200 mg/day was assessed in 30 patients with rheumatoid arthritis during an 8-weeks controlled study. Nimesil showed significant analgetic and antiinflammatory effects confirmed by decrease of pain, swollen and painful joint count. Effect was considered as good in 77% of cases. The drug was withdrawn in 3 patients because of side effects (gastrointestinal in 2 and face oedema in I)